(untitled) (Fiep Bulletin - online, 2017)
This article aimed to know the production of scientific knowledge about quality of life in children. The methodused was the integrative review. The databases consulted were SciELO, LILACS and MEDLINE. In total were found 47 articlespublished from 2006 to 2016. The results showed that the years biggest issue was the 2012 and 2013 with 7 articles published eachyear, the focus area with the largest number of articles published was medicine 16 articles and as the subject noticed a predominancein issues relating to quality of life of children diseases (78%) of published articles and only 4.7% related the most social issues. Thescientific literature on the quality of life of children is still focused on the biomedical model of health and there are few scientificproductions directed to the full model in health. Therefore, it is necessary to spread the production of scientific knowledge in the child’squality of life area in the context in which she lives and not just the disease, in which old research questions are giving way to newquestions and new paradigms health.